Experimental infection of severe combined immunodeficient (SCID) mice with the human microsporidian Trachipleistophora hominis - Koudela, B; Vávra, J; Canning, E U (Parasitology, 2004)
Different courses of microsporidiosis, related to the route of infection, were observed in severe combined immunodeficient (SCID) mice inoculated with spores of the human microsporidian Trachipleistophora hominis (Phylum Microspora). After eye contamination by spores the mice became moribund within 7 to 8 weeks, showing severe infection in the conjunctiva and cornea, and lighter infections in the urinary bladder, liver and spleen. The mean survival time of intramuscularly inoculated SCID mice was 12 weeks, when heavy infection was found in muscles around the site of inoculation, and also in several viscera. Subcutaneously inoculated SCID mice developed skin lesions around the inoculation sites, and heavy urinary bladder infection, and died 6 or 7 weeks after inoculation. Intracerebrally inoculated SCID mice became moribund 5 or 6 weeks after inoculation with massive infection in the urinary bladder and liver, but none in the brain. Intraperitoneally inoculated SCID mice survived for 13 weeks and the urinary bladder and liver were the most heavily infected organs. The SCID mice, inoculated perorally and examined after 23 weeks, were uninfected. Infection was not detected in the brain of any of the inoculated SCID mice. Our results show that T. hominis has very little tissue specificity. Peroral infection seems to be ineffective in T. hominis, but eye conta mination or insect bite (as mimicked by injection) are suggested as possible routes of infection under natural conditions.
Keywords: kosterní svaly; myši; mužské pohlaví; Microsporidia; elektronová mikroskopie; Male; Humans; Female; lidé; myši SCID; Spleen; oportunní infekce; ženské pohlaví; modely nemocí na zvířatech; Microscopy, Electron; Microsporidiosis; játra; Opportunistic Infections; imunokompromitovaný pacient; Animals; Immunocompromised Host; Mice, SCID; mikrosporidióza; zvířata; Mice; slezina; Muscle, Skeletal; Liver; Disease Models, Animal